Fire, people and pixels: linking social science and remote sensing to understand underlying causes and impacts of fires in Indonesia - Dennis, R.A.; Mayer, J.; Applegate, G.; Chokkalingam, U.; Colfer, C.J.P.; Kurniawan, I.; Lachowski, H.; Maus, P.; Permana, R.P.; Ruchiat, Y.; Stolle, F.; Suyanto; et al. (2005)
This study in the wake of 1990s fire catastrophes identifies and analyzes underlying causes of vegetation fires in eight locations across Borneo and Sumatra. Multidisciplinary and multiscale analysis integrates geospatial technologies with varied social research approaches and participatory mapping. It helps fill a void of site-specific evidence on diverse underlying causes of the Indonesian fires, despite emerging consensus on macrolevel causes and impacts, and policy debates on preventing future fire disasters. The most important findings include confirmation of multiple direct and underlying fire causes at each of the eight locations, no single dominant fire cause at any site, and wide differences in fire causes among sites. Conclusions emphasize the importance of location specific studies within a regional analytical context. This “hybrid” research methods demonstrate the explanatory power of integrating geospatial and social analysis techniques, and the benefits of analyzing fire causes and impacts at multiple scales in varied locations across diverse regions.